FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENABUNG (STUDI KASUS PADA BSI EX BSM JAKARTA TIMUR) - Renita Maharani (2021)
This research to analyze the effect of religiosity, product knowledge, service quality, location, and administrative costs on interest in saving at Bank BSI Ex BSM East Jakarta. The population selected in this study are customers who have an interest in saving at Bank BSI Ex BSM East Jakarta. The sample collection technique used is probability sampling with a type simple random sampling. The source of data in this study was obtained from distributing questionnaires to 130 respondents. The data analysis technique in this study uses SmartPLS 3.0. The results obtained from this study stated that (1) religiosity had a significant effect on interest in saving, (2) product knowledge had a significant effect on interest in saving, (3) service quality had no significant effect on interest in saving, (4) location had no significant effect on interest in saving. saving, and (5) administrative costs have no significant effect on interest in saving.